2021
DOI: 10.3390/rs13234738
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Rock Glacier Displacement in the Central Himalayas Using Multi-Temporal InSAR

Abstract: Rock glaciers represent typical periglacial landscapes and are distributed widely in alpine mountain environments. Rock glacier activity represents a critical indicator of water reserves state, permafrost distribution, and landslide disaster susceptibility. The dynamics of rock glacier activity in alpine periglacial environments are poorly quantified, especially in the central Himalayas. Multi-temporal Interferometric Synthetic Aperture Radar (MT-InSAR) has been shown to be a useful technique for rock glacier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…Relevant research has suggested [ 5 , 7 , 8 , 15 , 17 ] that the main factors for the climate and environment of mountain glaciers on the Qinghai-Tibet Plateau ice sheet and thus glacier morphology [ 47 , 48 ] include altitude, slope, slope orientation, rainfall, as well as glacier albedo. In addition, changes in surface organic carbon density due to human and natural activities can cause regional climatic and environmental changes [ 49 ], thus affecting glacier morphology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Relevant research has suggested [ 5 , 7 , 8 , 15 , 17 ] that the main factors for the climate and environment of mountain glaciers on the Qinghai-Tibet Plateau ice sheet and thus glacier morphology [ 47 , 48 ] include altitude, slope, slope orientation, rainfall, as well as glacier albedo. In addition, changes in surface organic carbon density due to human and natural activities can cause regional climatic and environmental changes [ 49 ], thus affecting glacier morphology.…”
Section: Resultsmentioning
confidence: 99%
“…However, the effective range of temperate glacier monitoring by conventional means is less than 1% due to the extreme climatic conditions and complex topography of the alpine ice sheet environment [ 15 ]. Currently, optical remote sensing is one of the critical tools adopted to generate regional inventories of mountain glaciers and extract glacier boundaries and area changes [ 16 , 17 ], whereas it is susceptible to natural cloud conditions, especially under the extreme climatic conditions of the ice sheet environment in alpine regions. Moreover, the effectiveness of optical remote sensing for mountain glacier monitoring has been poor [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sinusoidal model or the square root of the cumulative degree day of the freeze-thaw model has been commonly used to approximate seasonal oscillations. However, it is difficult to characterize the freeze-thaw process using a simple physical sinusoidal model, and the square root of the cumulative degree day model is generally constructed by a single point temperature, which cannot represent the deformation process on a large-scale [ 30 ]. Due to snow melt or vegetation dynamics (e.g., in alpine meadows), strong spatio-temporal decorrelation may occur in an interferometry network.…”
Section: Introductionmentioning
confidence: 99%